The firm as a pool of factor complementarities - Assar Lindbeck; Dennis J. Snower (Institute for International Economic Studies, 2003)
This paper presents a new approach to the theory of the firm by identifying factor complementarities as central to the determination of the firm's boundaries. The factor complementarities may take a variety of forms: technological and informational complementarities, as well as economies of scale and scope. We examine the tradeoff between the gains from these complementarities and transactions costs. In so doing, we must abandon the standard dichotomy between the determinants of plant size and firm size. The influence of factor complementarities on firm size is examined in partial and general equilibrium frameworks.
urn:nbn:se:su:diva-42116
Keywords: 330; Theorie der Unternehmung; Produktionsfaktor; Faktorsubstitution; Transaktionskosten; Betriebsgröße; Allgemeines Gleichgewicht; Theorie